Certain sufficient conditions for starlikeness and convexity using a multiplier transformation - BRAR, Richa; BILLING, Sukhwinder Singh (Studia Universitatis Babeș-Bolyai Mathematica, 2018)
In the present paper, we study a differential subordination involving a multiplier transformation. Selecting different dominants to our main result, we obtain certain sufficient conditions for starlikeness and convexity of analytic functions. In particular, we obtain the sufficient conditions for parabolic starlikeness and uniform convexity. Some known results appear as particular cases of our main result. Mathematics Subject Classification (2010): 30C80, 30C45.